The big fuzzy - Castle, Caroline; Howarth, Daniel (London : QED pub., 2007)
In cold, snowy Greenland, a little girl and her baby brother go ice fishing when their mother is sick, and when they get lost ina blizzard on the way home they find protection from an unexpected soucce
Keywords: Ice fishing -- Fiction; Fishing -- Fiction; Polar bear -- Fiction; Greenald -- Fiction